A Novel, Fast, Reliable, and Data-Driven Method for Simultaneous Single-Trial Mining and Amplitude—Latency Estimation Based on Proximity Graphs and Network Analysis - Dimitriadis, Stavros I.; Brindley, Lisa; Evans, Lisa H.; Linden, David E.; Singh, Krish D. (Frontiers in Neuroinformatics, 2018)
Both amplitude and latency of single-trial EEG/MEG recordings provide valuable information regarding functionality of the human brain. In this article, we provided a data-driven graph and network-based framework for mining information from multi-trial event-related brain recordings. On the first part, we provide the general outline of the proposed methodological approach. In the second part, we provide a more detailed illustration, present the obtained results on every step of the algorithmic procedure. To justify the proposed framework instead of presenting the analytic data mining and graph-based steps, we address the problem of response variability, a perquisite to reliable estimate both the amplitude and latency on specific N/P components linked to the nature of the stimuli. The major question addressed on this study is the selection of representative single-trials with main scope to uncover a less noised averaged waveform elicited from the nature of the stimuli. This graph and network-based algorithmic procedure increases the signal-to-noise (SNR) of the brain response, a key pre-processing step to reveal significant and reliable amplitude and latency at specific time after the onset of the stimulus and with the right polarity (N or P). We demonstrated the whole approach using EEG auditory mismatch negativity (MMN) recordings from 42 young healthy controls. The method is novel, fast and data-driven succeeding first to reveal the true waveform elicited by MMN on different conditions (frequency, intensity, duration, etc ). The proposed graph-oriented algorithmic pipeline increased the SNR of the characteristic waveforms and the reliability of amplitude and latency within the adopted cohort. We also demonstrated how different EEG reference schemes (REST vs average) can influence amplitude-latency estimation. Simulations results revealed robust amplitude-latency estimations under different SNR and amplitude-latency variations with the proposed algorithm.